Leadership Management of Human Resource Development in an Organization at an Educational Institution - Yohan Wibisono; Stefanus Sylvan Ryanto (PT. Alpha Trianguli Australis, 2025)
The quality of human resources is a determining factor in the success of an educational organization in achieving its institutional goals. In this context, leadership management plays a crucial role in directing, developing, and empowering the potential of individuals within the organization. This study aims to analyze the role of leadership management in human resource development in educational institutions. The study used a qualitative approach with literature study methods and conceptual analysis of various theories of leadership and human resource development. The results show that effective leadership management can create a conducive work environment, improve the professional competence of educators and education staff, and build an organizational culture that is adaptive to change. The implementation of visionary, participatory, and transformational leadership has been shown to have a significant impact on improving the quality of human resources in educational organizations. This study concludes that the success of human resource development in educational institutions is greatly influenced by the quality of leadership management that is able to integrate strategic planning, competency development, and strengthening an organizational culture oriented towards improving the quality of education.